EXPERIMENTAL INVESTIGATION ON THE PERFORMANCE CHARACTERISTICS OF R152A IN A VAPOR COMPRESSION REFRIGERATION SYSTEM - K.S. SRIDHAR RAJA, R. RAVISANKAR, C. THAMOTHARAN, N. KRISHNAMOORTHY, V. PUGAZHENTHI, MD JAVEED AHMED, RUBY PANT (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The growing environmental concerns and international restrictions on high-GWP refrigerants have accelerated the search for eco-friendly alternatives. This study presents an experimental investigation of R152a (1,1-difluoroethane) as a potential substitute for conventional refrigerants such as R134a and R22 in a vapor compression refrigeration system. The experimental setup was designed to evaluate system performance under varying evaporating (−10°C to 10°C) and condensing (35°C to 50°C) temperatures. Key parameters including coefficient of performance (COP), compressor power consumption, discharge pressure, and cooling capacity were analyzed. Results revealed that R152a delivered a COP improvement of 8–12% and a power reduction of 10–15% compared to R134a, with comparable cooling capacity and lower discharge pressure. Furthermore, R152a demonstrated a low Global Warming Potential (GWP = 124) and zero Ozone Depletion Potential (ODP = 0), confirming its suitability as a sustainable alternative refrigerant. The findings suggest that R152a can effectively replace high-GWP refrigerants in existing systems with minimal modifications, offering both energy efficiency and environmental benefits.